COELIAC PLEXUS NEUROLYSIS FOR PANCREATIC CANCER PATIENTS; RETROSPECTIVE ANALYSIS OF SHAUKAT KHANUM MEMORIAL CANCER HOSPITAL & RESEARCH CENTRE EXPERIENCE - Malik, Sara Haider; Hafeez, Haroon; Malik, Nimra Haider; Ghafoor, Ateeque Ur Rehman (Journal of Ayub Medical College Abbottabad, 2018)
Background: Among all the abdominal cancers, pancreatic cancer is the second most common one. Majority of the patients present with an excruciating pain when they are diagnosed with the disease. Coeliac plexus neurolysis (CPN) is a procedure that can control the pain in pancreatic cancer while precluding further consumption of analgesics in higher doses and quantity. The procedure of neurolysis is performed by injecting phenol/alcohol into the coeliac plexus ganglionic neural network. There is a high proportion of pain relief with CPN in up to 80% of the patients. Aim: The aim of our study is to assess the pain relief after CPN, reduction in analgesics consumption and evaluation of patient satisfaction post procedure. Methods: A cross sectional study was done and we collected the retrospective data from December 2016 to November 2017. A total of 35 patients of either gender (male and female) were included in this study. Neurolysis was done with transcrural approach using 6% phenol. Follow up of patients was done after 1 and 4 weeks of the procedure. The patients were evaluated for pain scores on numeric rating scale (NRS), reduction in analgesia and patient satisfaction regarding the procedure and pain relief. The analysis was based on mean values. Results: Total numbers of patients were 35. The mean age was 54.11±12.51 (SD) years with a male to female percentage of 31.43% and 68.57%. Follow up was done after 1 week and 4 weeks. Patients reported decrease in mean pain score (1 from 9 in Males and 0 from 9 in Females), reduction in analgesics (81.8% among Males and 18.2% among Females) and over all patient's satisfaction was (72.7% Males and 27.3% Females). Conclusion: It has been observed from the results that CPN works effectively for pancreatic cancer patients. There is a strong recommendation of neurolysis in patients with pancreatic cancer pain as it improves the pain scores, significant reduction in analgesia consumption with good patient satisfaction. Keywords: Coeliac plexus neurolysis; Pain scores; Patient satisfaction